A Miniaturized Hemoretractometer for Blood Clot Retraction Testing. Issue 29 (1st June 2016) - Li, Zida; Li, Xiang; McCracken, Brendan; Shao, Yue; Ward, Kevin; Fu, Jianping
Abstract : Blood coagulation is a critical hemostatic process that must be properly regulated to maintain a delicate balance between bleeding and clotting. Disorders of blood coagulation can expose patients to the risk of either bleeding disorders or thrombotic diseases. Coagulation diagnostics using whole blood is very promising for assessing the complexity of the coagulation system and for global measurements of hemostasis. Despite the clinic values that existing whole blood coagulation tests have demonstrated, these systems have significant limitations that diminish their potential for point‐of‐care applications. Here, recent advancements in device miniaturization using functional soft materials are leveraged to develop a miniaturized clot retraction force assay device termed mHemoRetractoMeter (mHRM). The mHRM is capable of precise measurements of dynamic clot retraction forces in real time using minute amounts of whole blood. To further demonstrate the clinical utility of the mHRM, systematic studies are conducted using the mHRM to examine the effects of assay temperature, treatments of clotting agents, and pro‐ and anti‐coagulant drugs on clot retraction force developments of whole blood samples. The mHRM's low fabrication cost, small size, and consumption of only minute amounts of blood samples make the technology promising as a point‐of‐care tool for future coagulation monitoring. Abstract : A miniaturized hemoretractometer is developed to measure dynamic clot retraction forces in real time using minute amounts of whole blood. This device takes advantage of interfacial behavior of blood samples for their localization between two free‐standing flexible beams serving as force sensors. Potential clinical applications of the hemoretractometer for whole‐blood measurements are demonstrated.